Using multimedia in large-scale computer-based testing programs. - Bennett, E. R.; Goodman, M.; Hessinger, J. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. The writers discuss the use of multimedia in large-scale computer-based testing programs. They contend that the effective measurement of problem solving and related cognitive constructs by future generations of tests will require the inclusion of tasks more like those actually encountered in academic work and settings. They assert that the advent of computer-based tests makes the inclusion of performance tasks more feasible. They suggest that the use of multimedia is one way in which some tasks might be made more relevant, particularly by incorporating dynamic stimuli. They offer examples of how stimuli, such as audio, video, and animation, might be utilized to assess skill in history, physical education, and the sciences. They then present an initial set of issues to be considered by operational testing programs.